2013
DOI: 10.2528/pierb13030406
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Distribution Modeling and Mapping of the Effective Earth Radius Factor for Microwave Link Design in South Africa

Abstract: Abstract-In this paper we present seasonal results of the effective earth radius factor distribution in South Africa using recently (2007)(2008)(2009) acquired radiosonde data from the South African Weather Service (SAWS) for seven locations in South Africa. Two data modeling methods are used to formulate the solution for the distribution of the effective earth radius factor.The seasonal effective earth radius factor statistics obtained from the radiosonde measurements are then interpolated, gridded and presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…In this paper, the two methods used are validated using the Root Mean Square error (RMSE) and the Mean Absolute Error (MAE). These errors are given by [6,14,17]:…”
Section: Interpolationmentioning
confidence: 99%
See 3 more Smart Citations
“…In this paper, the two methods used are validated using the Root Mean Square error (RMSE) and the Mean Absolute Error (MAE). These errors are given by [6,14,17]:…”
Section: Interpolationmentioning
confidence: 99%
“…This is achieved by making use of semivariogram modeling from which matrices are derived to enable the computation of the weights used in the prediction. The weights are then computed using the following relation [14,16]:…”
Section: Interpolationmentioning
confidence: 99%
See 2 more Smart Citations
“…In the bid to improve on the coverage, capacity and quality of service for radio wave communication systems, experts have found that the propagation of radio signals through the atmosphere is greatly influenced by the effective earth radius factor k [5,6,7,8]. Particularly, the k-factor is largely dependent on one of the most important parameters of radio wave propagation known as refractivity gradient as considered in the lowest 65m from the ground level [9,10,11]. Variations in refractivity may cause radio waves to bend while propagating through dissimilar layers of the atmosphere [12].…”
Section: Introductionmentioning
confidence: 99%